Motivasi kerja pegawai pada kantor pencarian dan pertolongan kelas A Kupang (BASARNAS) - Issu, Elviana Vivi (P3M- Politeknik Negeri Kupang, 2019)
The Study of Staff Work Motivation in The Office of Research and Rescue Class A Kupang (BASARNAS). The aim of the research was to know how the staff work motivation in the office of Research and Rescue Class A Kupang (BASARNAS). The research method used data analysis technique, that was descriptive qualitative method by using the descriptive statistic that is the mean value or the average of median on the stage of question items. The population in this research were all the staff in the office of Research and Rescue Class A Kupang (BASARNAS ) , that amounted 68 people and all the 68 staff became the samples. The obtained result in this research showed that the work motivation was catagorized in very good, that was the total amount of score 2.766 was divided by ideal score 3.400 then multiplied by 100% = 81,35%, it stated that the staff work motivation in the office of Research and Rescue Class A Kupang (BASARNAS ) was very good Keywords : Staff Work Motivation